Autophagy Is Involved in Stellate Ganglion Block Reversing Posthemorrhagic Shock Mesenteric Lymph-Mediated Vascular Hyporeactivity - Wang, Chen; Du, Hui-Bo; Zhao, Zhen-Ao; Zhai, Jia-Yi; Zhang, Li-Min; Niu, Chun-Yu; Zhao, Zi-Gang (Frontiers in Physiology, 2021)
Objective: To clarify the role of autophagy in stellate ganglion block (SGB) reversing post-hemorrhagic shock mesenteric lymph (PHSML)-mediated vascular hypo-reactivity. Methods: Hemorrhagic shock model in conscious rats was employed to observe the effects of SGB (0.2 mL of 0.25% ropivacaine hydrochloride hydrate) and autophagy inhibitor 3-MA (30 mg/kg) on the vascular reactivity of second order rat mesenteric arteries in vitro, while the effects of PHSML (1 mL/kg) and autophagy agonist rapamycin (Rapa, 10 mg/kg) on the beneficial effect of SGB were investigated. The cellular viability, contractility and autophagy related protein expressions in vascular smooth muscle cells (VSMCs) were detected following treatments of PHSML, PHSML obtained from rats underwent hemorrhagic shock plus SGB (PHSML-SGB), and PHSML plus 3-MA (5 mM), respectively. Results: Hemorrhagic shock significantly decreased the vascular reactivity to gradient NE, which is reversed by the SGB treatment and 3-MA administration. On the contrary, PHSML intravenous infusion and Rapa administration inhibited the vascular contractile responses in rats underwent hemorrhagic shock plus SGB treatment. PHSML treatment significantly inhibited the cellular viability and contractility in VSMCs, increased the expressions of LC3-II and Beclin1, and decreased the expression of p62, along with opposite appearances in these indices following PHSML-SGB treatment. In addition, 3-MA counteracted the adverse roles of PHSML in these indices in VSMCs. Conclusion: SGB inhibits PHSML-mediated vascular hypo-reactivity by reducing the excessive autophagy in VSMCs.